Bruno Latour in the Semiotic Turn An Inquiry into the Networks of Meaning - Peverini, Paolo; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2024)
This open access book highlights the link between Bruno Latour's works and the semiotic perspective on social phenomena analysis. It identifies and relaunches a dialogue that was as heated as it was fruitful, but still little recognized within the social sciences. It asks why the theory of signification has so far been only sporadically acknowledged in literature derived from Latour's work. Starting from these premises, the book explores two interrelated dimensions, the initial one of a "semiotics for Latour", which looks at concepts from semiotics in Latour's study of social phenomena, and extensively for the first time, a symmetrical one of a "Latour for semiotics," accounting for the impact of Latourian inquiry on contemporary semiotic research. The book offers a novel perspective on Bruno Latour's work by addressing a wide readership, including those interested in Latour$1 (Bs approach, actor-network theory, semiotics, and the social sciences. The English translation of this book from the Italian original manuscript was done with the help of artificial intelligence, then revised technically and linguistically by the author in collaboration with a professional translator. .s
Acknowledgments -- 1. Introduction -- 2.Narrative semiotics and the study of scientific practices -- 3.Semiotics for Actor Network Theory -- 4.Enunciation -- 5.Latour for semiotics.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Sociology; Ethnology; Semiotics; Sociological Theory; Sociocultural Anthropology; Semiotics